Optimisation of thermal performances in livestock housing design solutions using genetic algorithms. (2015) - Menconi, Maria Elena; Chiappini, Massimo; Grohmann, David
Various design elements can affect the energy efficiency of buildings. Usually, parametric analysis does not take into account the interactive effects between the different features in terms of building energy use. Genetic algorithm (GA)-based optimisation approach relies on the evolutionary concept of natural selection to converge on an optimal solution and links together many parameters and several solutions. This methodology is well documented in residential buildings but, so far, few tries were made to extend this process to livestock housing and service facilities. In this paper, genetic algorithms are applied as an optimisation tool to find suitable design solutions in terms of thermal performance. This process is applied to a simple sheepfold model located in Mediterranean climate for a medium-size extensive enterprise. The study analyses only passive design solutions.